Global social archaeologies - Mizoguchi, Kōji, 1963- author.
1 online resource
Keywords: "Global Social Archaeologies contributes to the active engagement of contemporary social archaeology with issues of postcolonialism, community heritage, and indigenous rights and the major challenge that it faces in breaking down global divides, especially in relation to fundamental human rights, inequality and inequities of wealth, power, and access to knowledge"--